1990
DOI: 10.1071/ar9900583
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for wool production and quality traits in South Australian Merinos of the Collinsville family group

Abstract: Heritabilities and phenotypic and genetic correlations for fleece traits were estimated from a data set comprising 805 male and female progeny of 44 sires of the Collinsville family group. Characteristics included in the study were greasy and clean fleece weight, yield, mean, standard deviation and coefficient of variation of fibre diameter, resistance to compression, scoured and greasy wool colour (expressed as yellowness, lightness and yellowness index), wax content, suint content, and subjectively assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
6
15
1
Order By: Relevance
“…A heritability of 0.55 ± 0.16 for scoured wool brightness (yY) has also been reported (James et al, 1990). There is a similar range of estimates of heritability for greasy color measurements (James et al, 1990;Raadsma and Wilkinson, 1990).…”
Section: Heritabilitymentioning
confidence: 56%
“…A heritability of 0.55 ± 0.16 for scoured wool brightness (yY) has also been reported (James et al, 1990). There is a similar range of estimates of heritability for greasy color measurements (James et al, 1990;Raadsma and Wilkinson, 1990).…”
Section: Heritabilitymentioning
confidence: 56%
“…These estimates of heritability for the wool production and wool quality traits are generally consistent with those reviewed by Safari et al (2005) and more recent reports from large Merino data sets (Asadi Fozi et al, 2005;Safari et al, 2007a;Swan et al, 2008Swan et al, , 2016Brown et al, 2010Brown et al, , 2013. The few reports of estimates for heritability of scoured wool yellowness color (Y-Z) in Merino sheep range from 0.25 for yearlings and 0.29 for adults (Smith and Purvis, 2009) to 0.42 ± 0.14 (James et al, 1990) and 0.45 ± 0.08 (Hebart and Brien, 2009), with estimates from Coopworth and Romney sheep being lower (0.13 ± 0.06; Bigham et al, 1983). A heritability of 0.55 ± 0.16 for scoured wool brightness (yY) has also been reported (James et al, 1990).…”
Section: Heritabilitymentioning
confidence: 99%
“…The few reports of estimates for heritability of scoured wool yellowness color (Y-Z) in Merino sheep range from 0.25 for yearlings and 0.29 for adults (Smith and Purvis, 2009) to 0.42 ± 0.14 (James et al, 1990) and 0.45 ± 0.08 (Hebart and Brien, 2009), with estimates from Coopworth and Romney sheep being lower (0.13 ± 0.06; Bigham et al, 1983). A heritability of 0.55 ± 0.16 for scoured wool brightness (yY) has also been reported (James et al, 1990). There is a similar range of estimates of heritability for greasy color measurements (James et al, 1990;Raadsma and Wilkinson, 1990).…”
Section: Heritabilitymentioning
confidence: 99%
“…Surprisingly, Barlow (1974) and Wuliji et al (1993) reported no significant differences in CWC in progeny of high fleece weight selected Peppin Merino and Romney ewes, respectively, and random control flocks. On the other hand, a negative genetic correlation between CFW and CWC found in Collinsville Merinos (James et al, 1990) indicated that CWC would improve under selection for higher CFW. The positive genetic correlation estimates between YPC and fleece weights found here also disagree with the findings of Wilkinson and Aitken (1985) who reported negative genetic correlations for YPC with GFW and CFW of -0.41 ± 0.35 and -0.71 ± 0.35, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the genetics of wool yellowing have found that the heritability of clean wool colour (CWC) -measured in Y-Z units -varies from 0.04 ± 0.07 in Romney sheep in New Zealand (Hawker et al, 1988) to 0.42 ± 0.14 for Collinsville Merinos in Australia (James et al, 1990). The variation between these heritability estimates might have been due to environmental variation caused by differences in weather conditions between the locations of these studies.…”
Section: Introductionmentioning
confidence: 99%